Literasi Aspek Permodalan dan Penyusunan Kelayakan Usaha Peternakan Sapi di Desa/Nagori Bahjoga - Zul Azmi; Arfan Ikhsan Lubis; Sari Bulan Tambunan; Hendra Harmain (Asosiasi Dosen Akuntansi Indonesia, 2021)
This community service aims to improve literacy aspects of capital and the preparation of the feasibility of a cattle farming business in the Village/Nagori Bahjoga. The implementation method used in this community service activity uses the method of socialization, training / counseling to participants accompanied by direct discussions with training participants, namely business actors in cattle farmer groups and individuals, and training in preparing business feasibility so that cattle breeders become bankable. The result achieved is that cattle breeders can understand the form of capital financing services. Business actors in the cattle breeder group can also prepare business feasibility in the form of a business feasibility proposal.